The Effect Of Purple Sweet Potato (Ipoema Batatas L) Extract On Levels Of Lipoprotein-Associated Phospolipase A2 (Lppla2) Male White Rats (Rattus Norvegicus Strain Wistar) Atherosclerosis Model - Meddy Setyawan; Mochammad Ma’roef; Aflah Al Faiyq; Enggar Yusrina Hasyyati (Universitas Muhammadiyah Malang, 2023)
Atherosclerosis is the primary etiology of coronary heart disease and can be detected by marker of LpPLA2. There is a unique phenomenon in Papua: patients of CHD in Papua are the lowest amount in Indonesia, although they consume a lot of cholesterol from pigs. This is expected because the Papuans consume purple sweet potato that contains antioxidants to prevent atherosclerosis. The objective of this experiment is to prove that the Purple Sweet Potato Extract (Ipoema Batatas L.) has a significant effect on Lp-PLA2 in the White Male Rats (Rattus novergicus Wistar strain) Model of Atherosclerosis. This study applied experimental research using Post Test Only Control Group Design with a large sample of 35 rats divided into five groups with the inclusion criteria. Variables taken for this experiment are LpPLA2 ‘s levels of positive control, negative control, and the treatment from groups 1,2 and 3. Methods of assessment LpPLA2 levels by Elisa-kit. Analysis of the test data using one-way ANOVA, post-hoc, and correlations. The higher the dose of the extract of purple sweet potato is given, the lower the levels of LpPLA2 mice. The effect of extract of purple sweet potato (Ipoema batatas) can reduce levels of LpPLA2 white male rats (Rattus novergicus Wistar strain) model of atherosclerosis.